Nano-enzyme for enhancing peroxidase reaction through photocatalysis cascade and preparation method and application of nano-enzyme
The three-dimensional flower-like nanoenzyme CuCo(OH)2 synthesized by a simple hydrothermal method solves the problem of low catalytic efficiency of existing nanoenzymes, achieves efficient reactive oxygen species generation and excellent antibacterial properties, and has significant effects on drug-resistant bacteria.
Patent Information
- Application Number
- CN202411853700.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-16
AI Technical Summary
When existing nanoenzymes catalyze peroxidase reactions, the single functionality and limited catalytic efficiency limit their application in the field of antibacterials, especially in the fight against drug-resistant bacteria.
The three-dimensional flower-like nanoenzyme CuCo(OH)2 was synthesized by a simple one-step hydrothermal method. Co(OH)2, which formed rich oxygen vacancies, promoted the adsorption of H2O2, and enhanced photogenerated electron transfer under visible light irradiation to generate reactive oxygen species (ROS), thereby improving the efficiency of POD reaction.
It achieved efficient reactive oxygen species (ROS) generation and excellent antibacterial properties. The elimination rate of Gram-negative E. coli (E. coli) produced by resistant bacteria exceeds 99.999%, and demonstrated excellent in vivo antibacterial activity and biocompatibility.
Smart Images

Figure CN119587581A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of medical technology, and specifically relates to a nanozyme for photocatalytic cascade enhanced peroxidase reaction, and a preparation method and use thereof. Background Art
[0002] Improper use of antibiotics may lead to the emergence of drug-resistant bacteria. Drug-resistant bacterial infections have become a common and complex clinical problem, posing a serious threat to human health. Reactive oxygen species (ROS), as a promising antimicrobial active substance, can effectively eliminate bacteria by inducing oxidative stress while reducing the possibility of bacterial resistance. Since the discovery of ferrite (Fe3O4) nanoparticles with peroxidase (POD)-like activity, nanozymes have become an emerging field, among which POD-like nanozymes have become promising candidates for eliminating drug-resistant bacteria by catalyzing H2O2 to generate hydroxyl radicals (•OH). Compared with biological enzymes, nanozymes are reusable, low-cost, stable, and easy to control in terms of morphology and composition. However, the single functionality and limited catalytic efficiency of nanozymes are still inferior to those of biological enzymes, limiting their development and application.
[0003] The key steps in the generation of •OH in the POD reaction include the adsorption of H2O2 at the active site, electron transfer, and desorption of •OH. It is very important to improve the adsorption of H2O2 at the active site. At present, the regulation of nanozyme catalysts mainly revolves around strategies such as constructing diverse nanostructures, introducing vacancies or defects, doping, and crystal engineering. Among them, oxygen vacancies (Ov), as a common defect type in nanomaterials, play a vital role in heterogeneous catalysis, and nanomaterials rich in oxygen vacancies have good adsorption effects on H2O2 and O2. For example, Yu et al. significantly enhanced the number of oxygen vacancies on the surface of molybdenum oxide (Fe-MoOV) by iron doping. This enhancement significantly improved the adsorption and dissociation efficiency of H2O2, thereby enhancing its oxidase and peroxidase-like activity.
[0004] Typically, POD-like nanozymes undergo OO cleavage to generate •OH via a Fenton-type mechanism. Light energy excites electron transitions and promotes the directional migration of excited electrons from organic ligands to metal atoms, thereby accelerating Fenton or Fenton-like reactions. In recent years, the unique optical properties of nanomaterials have become a hot topic of research. Combining the optical properties of nanozyme materials with enzyme-like activity to form a light-enhanced catalytic system has attracted widespread attention due to its controllability and high efficiency. Ultraviolet (UV) nanozymes exhibit excellent catalytic performance due to their high photon energy. However, severe DNA damage limits their application. Therefore, visible light nanozymes with cost-effectiveness and excellent biocompatibility have become a more ideal alternative. The short ROS lifetime and limited diffusion distance are also factors that weaken the antibacterial properties of nanozymes. Due to electrostatic interactions, positively charged nanomaterials tend to adsorb to negatively charged bacterial membranes, which has been confirmed in early studies, such as positively charged gold nanorods and gold nanorods modified with cetyltrimethylammonium bromide (CTAB). Therefore, the development of positively charged light-enhanced nanozyme systems that can efficiently generate ROS is expected to become an effective strategy for inactivating drug-resistant bacteria. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention provides a nanozyme for photocatalytic cascade enhanced peroxidase reaction and its preparation method and use. A three-dimensional (3D) flower-shaped nanozyme CuCo(OH)2, Co 2+ Cu 2+ The ions form hydroxide compounds through a hydrolysis process, which further grow to form a three-dimensional hierarchical flower-like structure with extremely thin corrugated nanosheets. Copper-doped Co(OH)2 has efficient reactive oxygen species (ROS) generation and excellent antibacterial properties.
[0006] The technical solution provided by the present invention is: a nanozyme for photocatalytic cascade enhanced peroxidase reaction, wherein the nanozyme is a copper-doped nanozyme CuCo(OH)2, wherein the doping amount of Cu in CuCo(OH)2 is 3-5%.
[0007] Preferably, the doping amount of Cu in CuCo(OH)2 is 3.96%.
[0008] The present invention further provides a method for preparing the copper-doped nanozyme, comprising: dissolving Co(NO3)2•6H2O and Cu(NO3)2•3H2O in methanol, and dissolving 2-methylimidazole in methanol; then, quickly pouring the 2-MIM solution into a solution containing Co 2+ and Cu 2+The mixture was added to a solution and stirred evenly with a magnetic force; in the reaction system, the final concentration of Co(NO3)2•6H2O was 50-100 mmol / L, the final concentration of Cu(NO3)2•3H2O was 20-50 mmol / L, and the final concentration of 2-methylimidazole was 150-200 mmol / L; the mixed solution was then transferred to a PTFE-lined stainless steel autoclave and heated at 120°C for 2 hours; after cooling to room temperature, the precipitate was washed several times with methanol by centrifugation, and then dried at 60°C to collect the yellow product.
[0009] The present invention also provides the use of the nanozyme, and the use of the nanozyme in the preparation of an antibacterial composition.
[0010] Preferably, the nanozyme is used in the preparation of a composition for fighting drug-resistant bacteria.
[0011] The present invention further provides an antibacterial composition, comprising an effective dose of the nanozyme, wherein the nanozyme promotes the generation of ROS in the photocatalytic cascade enhanced POD reaction.
[0012] The copper-doped nanozyme Co (OH)2 provided by the present invention forms abundant oxygen vacancies, which promotes the adsorption of H2O2. Subsequently, the CuCo(OH)2 system enhances the photogenerated electron transfer, generates •OH to promote the POD reaction, and enhances the O2• - and 1 O2 generation. The light-enhanced POD-like enzyme activity enables CuCo(OH)2 to have efficient reactive oxygen species (ROS) generation and excellent antibacterial properties. In addition, the present invention also demonstrates its excellent in vivo antibacterial activity and biocompatibility, indicating its potential in the treatment of drug-resistant bacterial infections and has broad clinical application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 Schematic diagram of light / enzyme synergistic catalytic mechanism and wound healing / antibacterial mechanism; (a) light / enzyme synergistic catalytic mechanism; (b) wound healing and antibacterial mechanism; Figure 2Characterization spectrum of CuCo(OH)2; including: (a) scanning electron microscope (SEM) image of CuCo(OH)2 nanoflowers; (b) transmission electron microscope (TEM) image of CuCo(OH)2 nanoflowers; (c) high-resolution transmission electron microscope (HRTEM) image of CuCo(OH)2 nanoflowers; (d) element distribution map image of CuCo(OH)2 nanoflowers; (e) X-ray diffraction (XRD) spectrum of Co (OH)2 and CuCo(OH)2; (f) high-resolution copper (Cu) 2p X-ray photoelectron spectrum of CuCo(OH)2; (g) high-resolution cobalt (Co) 2p X-ray photoelectron spectrum of Co (OH)2 and CuCo(OH)2; Figure 3 Energy dispersive spectroscopy (EDS) of CuCo(OH)2; Figure 4 It is the full scan spectrum of X-ray photoelectron spectroscopy (XPS) of Co (OH)2 and CuCo(OH)2; Figure 5 High-resolution O1s X-ray photoelectron spectroscopy of Co (OH)2 and CuCo(OH)2; Figure 6 The POD-like activity and optical properties of CuCo(OH)2 were determined; (a) the POD activity of CuCo(OH)2 / H / L, Co (OH)2 / H / L, CuCo(OH)2 / H and Co (OH)2 / H was characterized by a tetramethylbenzidine (TMB)-based method; (b) the electron paramagnetic resonance (EPR) spectra of Co(OH)2 and CuCo(OH)2; (c) the UV-visible reflectance spectra of Co(OH)2 and CuCo(OH)2; (d) the electron paramagnetic resonance (EPR) spectra of Co(OH)2 and CuCo(OH)2 for detecting •OH in the presence of 5,5-dimethyl-1-pyrroline-N-oxide (DMPO); (e) the singlet oxygen (EO) spectra of Co(OH)2 and CuCo(OH)2 in the presence of 2,2,6,6-tetramethylpiperidine (TEMP) 1 O2) and (f) in the presence of 5,5-dimethyl-1-pyrroline-N-oxide (DMPO) for the detection of superoxide anion radicals (O2• - ), H represents H2O2; L represents visible light; the illumination time is 10 minutes; Figure 7Figure 2 is the antibacterial activity test of CuCo(OH)2; (a) Bacterial culture results of ESBL-producing Escherichia coli treated with different methods, H2O2 and visible light; (c) SYTO 9 and propidium iodide (PI) staining of ESBL-producing Escherichia coli; (d) Scanning electron microscopy (SEM) image of ESBL-producing Escherichia coli morphology; (e) Protein leakage of ESBL-producing Escherichia coli incubated with different methods, A: Co(OH)2 / H, B: CuCo(OH)2 / H, C: Co(OH)2 / H / L, D: CuCo(OH)2 / H / L; (f) DNA agarose gel electrophoresis of ESBL-producing Escherichia coli treated with different methods; (g) In vitro cytotoxicity characteristics of L929 cells incubated with different concentrations of CuCo(OH)2 / H / L; (g) Effects of different treatments on cell migration (scale bar, 200 μm); (h) Statistical data of scratch width in different treatment groups, error bars represent standard deviation (n = 3); *** indicates p < 0.001; H represents H2O2; L represents visible light; illumination time is 10 min; Figure 8 is the survival of ESBL-producing E. coli under different treatments; Fig. 9 The effect of CuCo(OH)2 on wound healing was tested; (a) images of back wounds of rats treated with different methods, A: Co(OH)2 / H, B: CuCo(OH)2 / H, C: Co(OH)2 / H / L, D: CuCo(OH)2 / H / L; (b) bacterial samples collected from treated wounds; (c) relative wound areas of different groups on the 10th day and (d) the number of bacteria in the wounds; error bars represent standard deviations (n = 3); *** indicates p < 0.001; (e) H&E staining data of corresponding skin wounds after various treatments; (f) immunohistochemical images of rat wounds; (g) H&E sections of major organs (heart, liver, spleen, lungs and kidneys) of mice in different groups on the 10th day; H represents H2O2; L represents visible light; and the illumination time is 10 minutes. DETAILED DESCRIPTION
[0014] In order to facilitate the understanding of this research, the following is a more detailed description of this research in conjunction with the accompanying drawings and specific embodiments. However, this research can be implemented in many different forms and is not limited to the embodiments described in this specification. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of this research more thorough and comprehensive.
[0015] The present invention proposes a nanozyme for photocatalytic cascade enhancement of peroxidase reaction and a photocatalytic cascade enhancement of POD reaction strategy, using CuCo(OH)2, a copper-doped nanozyme rich in oxygen vacancies and positively charged, to promote the generation of ROS for antibacterial treatment. Studies have shown that copper-doped Co(OH)2 forms abundant oxygen vacancies, which promotes the adsorption of H2O2. Subsequently, the CuCo(OH)2 system enhances the photogenerated electron transfer, generates •OH to promote the POD reaction, and enhances the O2• - and 1 The generation of O2, such as Figure 1 As shown in (a). The light-enhanced POD-like enzyme activity of CuCo(OH)2 has efficient ROS generation and excellent antibacterial properties, with an elimination rate of more than 99.999% for ESBL-producing Gram-negative Escherichia coli (E. coli) and its excellent antibacterial properties accelerate wound healing. Further antibacterial mechanism shows that ROS can cause cell membrane damage and DNA degradation, thereby causing irreversible cell death, such as Figure 1 In addition, the excellent antibacterial activity and biocompatibility of CuCo(OH)2 in vivo suggest its potential in the treatment of drug-resistant bacterial infections.
[0016] 1. Reagents and Materials
[0017] Cobalt nitrate hexahydrate (Co(NO3)2•6H2O), copper nitrate hydrate (Cu(NO3)2•3H2O), 2-methylimidazole (2-MIM), and methanol were purchased from Sinopharm Chemical Reagent Co., Ltd. Hydrogen peroxide (H2O2) and 3,3′,5,5′-tetramethylbenzidine (TMB) were purchased from Aladdin Chemical Reagent Co., Ltd. (Shanghai, China). Live / Dead BacLight Bacterial Viability and Counting Kit was purchased from Thermo Fisher, USA. BCA Protein Concentration Assay Kit was purchased from Elabscience Biotechnology Co., Ltd. TIANamp Bacterial DNA Extraction Kit was purchased from Tiangen Biochemical Technology (Beijing) Co., Ltd. Ultrapure water with a resistivity of 18.2 MΩ·cm was used in all experiments. All chemical reagents were of commercial quality and used directly without further purification.
[0018] 2. Sample Synthesis
[0019] (1) Synthesis of Co(OH)2
[0020] A simple one-step solvothermal method was used to synthesize three-dimensional flower-like Co(OH)2. Specifically, 3 mmol Co(NO3)2•6H2O and 4 mmol 2-MIM were dissolved in 25 mL methanol. Then, the 2-MIM solution was quickly poured into the Co 2+The mixture was then transferred to a 100 mL polytetrafluoroethylene (PTFE) lined stainless steel autoclave and heated at 120°C for 2 hours. After cooling to room temperature, the precipitate was washed several times with methanol by centrifugation and then dried at 60°C to collect the yellow product.
[0021] (2) Synthesis of CuCo(OH)2
[0022] A simple one-step solvothermal method was used to synthesize three-dimensional flower-like CuCo(OH)2. Specifically, 2 mmol Co(NO3)2•6H2O and 1 mmol Cu(NO3)2•3H2O were dissolved in 25 mL methanol, and 4 mmol 2-MIM was dissolved in 25 mL methanol. Subsequently, the 2-MIM solution was quickly poured into a liquid containing Co. 2+ and Cu 2+ The mixture was then transferred to a 100 mL PTFE-lined stainless steel autoclave and heated at 120°C for 2 hours. After cooling to room temperature, the precipitate was washed several times with methanol by centrifugation and then dried at 60°C to collect the yellow product.
[0023] 3. Characterization
[0024] To investigate the microstructure of the samples, scanning electron microscopy (SEM) images and energy dispersive X-ray spectroscopy (EDS) elemental mapping / line scanning were obtained on a Sigma 500 (200 kV). Transmission electron microscopy (TEM) and high-resolution TEM (HR-TEM) images were acquired using a JEM-2100F. The crystal structures of the samples were measured by X-ray diffraction (XRD, SmartLab 3KW) using Cu Ka radiation at a scan rate of 10° / min. X-ray photoelectron spectroscopy (XPS) data were obtained using a Thermo VG Scientific ESCALAB 250 spectrometer. UV–visible absorption spectra were detected using a Mapada UV-6300 spectrophotometer (Shanghai, China). Electron spin resonance (ESR) spectra were evaluated using a Bruker A300-10 at 77 K. A microplate reader was purchased from Thermo Fisher Scientific. The zeta potential was measured using a Malvern nanoparticle potentiometer. Bacterial flow cytometry data were measured by FACS Celesta flow cytometer, and live / dead bacterial tests were observed using a fluorescence microscope (Nikon ECLIPSE Ni-U, Japan).
[0025] 4. Electrochemical Measurement
[0026] (1) Characterization of POD-like activity
[0027] The POD-like catalytic activity of the samples was evaluated in an acetate buffer system containing 50 μL TMB (20 mM) and 10 μL H2O2 (100 mM) in the presence of 50 μL nanozyme (250 μg / mL), and the absorbance of the reaction system was measured at 652 nm. The absorbance was determined using an ELISA plate reader.
[0028] (2) Free radical scavenging test
[0029] The free radical species were detected by electron spin resonance technique (EPR) using 5,5-dimethyl-1-pyrrolidine (DMPO) and 2,2,6,6-tetramethyl-4-piperidinol (TEMP) as trapping agents. The detailed parameters are as follows: 100 μL of the sample water suspension was mixed with 1.0 mL of TEMP (50.0 mM) solution. •OH trapping-EPR test was also performed as described above, the only difference being that DMPO (50.0 mM) was used as the trapping agent. For O2• - , 1 mL of methanol and water (volume ratio 20:1) was mixed with a solution containing DMPO (50.0 mM).
[0030] 5. Bacterial culture
[0031] In this study, extended-spectrum β-lactamase-producing Escherichia coli (ESBL-producing E. coli) was used as a model organism. Hospital wastewater was obtained from a hospital in Qingdao, and airborne bacteria were collected in a microbiology laboratory. Monoclonal bacteria were cultured on Luria-Bertani (LB) solid medium and transferred to 50 mL of LB liquid medium and cultured at 37 °C, 150 rpm for 12 h until the logarithmic growth phase was reached.
[0032] VI. In vitro antibacterial test of CuCo(OH)2
[0033] More than three bacterial colonies were randomly selected on LB solid medium, inoculated into 50 mL sterile LB liquid medium, and cultured at 37°C, 150 rpm for 12 h. The suspension was then diluted to 0.5 MCF (McFarland) using a McFarland turbidimeter with sterile saline. 0.5 MCF corresponds to 1×10 8 CFU / mL. Then dilute the bacterial suspension to 1×10 6CFU / mL. The bacterial suspension (500 μL) containing different concentrations of nanozymes was incubated at 37°C for 30 minutes, 10 μL H2O2 (100mM) was added, and irradiated under visible light for 10 minutes. The incubated bacterial liquid was taken out of the water bath, and 100 μL of bacterial suspension was evenly spread on the solid LB culture medium and spread evenly with a coating rod. After the culture plate was placed vertically for 30 minutes, it was inverted and cultured in a 37°C incubator for 24 hours. Each group of experiments was repeated three times.
[0034] 7. Live / dead bacteria detection
[0035] To further observe the effect of ROS on ESBL-producing Escherichia coli, the bacteria were labeled with Syto 9 / PI fluorescent probe. After culturing the bacteria for 12 hours, 500 μL of bacterial suspension was taken and washed twice with PBS (pH 7.4). The bacterial suspension was then treated with different concentrations of CuCo(OH)2 for 30 minutes, centrifuged at 3000 rpm for 5 minutes at 37°C, and the precipitate was retained and washed twice. Finally, 25 μL of Syto 9 / PI dye mixture was added, incubated for 15 minutes, and observed with a normal upright fluorescence microscope.
[0036] 8. Bacterial protein leakage test
[0037] The bacteria were cultured in liquid culture medium for 12 hours, and 500 μL of bacterial suspension was taken and washed twice with PBS (pH 7.4). The bacterial suspension was then treated with different concentrations of CuCo(OH)2 for 30 minutes, centrifuged at 8000 rpm for 5 minutes at 37°C, and the cell-free supernatant was collected. The protein concentration in the supernatant was determined using the BCA protein concentration assay kit according to the instructions.
[0038] IX. DNA Degradation Experiment
[0039] ESBL-producing E. coli were treated with CuCo(OH)2 for 30 min and then washed twice with PBS (pH 7.4). Bacterial DNA was extracted using a DNA extraction kit, the DNA concentration was measured, and the same concentration of DNA was loaded and finally identified using agarose gel electrophoresis.
[0040] 10. Bacterial morphology detection
[0041] In order to observe the changes in bacterial morphology after CuCo(OH)2 treatment, the treated ESBL-producing E. coli strains were collected and centrifuged at 3000 rpm for 15 min. Single colonies were cultured on LB medium until OD 600 Reach 1.0. by centrifugation 1.5 mLOD 600The bacterial solution reached 1.0, the enriched bacteria were collected and washed three times with PBS (pH 7.4). Then two groups of bacteria were treated as: a) bacteria only; b) bacteria + CuCo(OH)2 / H2O2 / light (lighting time 10 minutes). The above treatment groups were incubated at 37°C for 5 hours, then washed three times with PBS (pH 7.4), and the precipitates were collected, fixed with 2.5% glutaraldehyde for 1 hour and stored at 4°C. Subsequently, the fixative was washed with PBS (pH 7.4) and dehydrated with 30%, 50%, 70%, 90% and 100% ethanol in sequence for 15 minutes each, and then treated with 50% ethyl acetate. Finally, the bacterial cells were characterized using an S-4700 scanning electron microscope (Hitachi, Japan).
[0042] XI. In vitro toxicity test
[0043] To evaluate the cytotoxicity of the prepared CuCo(OH)2, mouse L929 fibroblasts were used as a cell model, and cell viability was determined by the standard 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) method. The cells were cultured in 96-well plates for 24 hours and then treated with different concentrations of CuCo(OH)2 / H2O2 / light. After 24 hours of incubation, 10 μL of MTT solution was added to each well and incubated for another 4 hours. Finally, 10 μL of DMSO was added to each well and incubated for another 4 hours. The absorbance value was measured at 490 nm using a microplate reader.
[0044] 12. In vitro scratch healing experiment
[0045] The migration ability of cells was evaluated by scratch test. L929 cells (4 × 10 5 Cells / well) were seeded in a 6-well plate. When the cells grew to 80% confluence, three uniform scratches were made using a 200 μL pipette tip, and then washed twice with PBS (pH 7.4), 2 mL of serum-free medium was added, and Co(OH)2 / H2O2 / light and CuCo(OH)2 / H2O2 / light at a concentration of 12.5 mg / mL were added. Microscopic photographs were taken at the same position every 12 hours, 24 hours, and 48 hours to evaluate cell migration. Cell migration rate × (%) = (0 hour scratch width - scratch width after culture) / 0 hour scratch width × 100%.
[0046] 13. Animal Experimentation
[0047] Sprague Dawley (SD) rats and Kunming mice (KM) (6 weeks old) were purchased from Beijing Sipeifu Biotechnology Co., Ltd. All experiments involving animals were approved by the Ethics Committee of Qingdao University Medical College. After the rats were anesthetized with 20% urea, a 1 cm diameter circular punch was used to make a wound model on the back of the rats, and then 20 μL, 1×10 6 CFU / mL of ESBL-producing Escherichia coli was dripped into the wound. The wound was then treated with 10 μL of 12.5 mg / mL Co(OH)2 / CuCo(OH)2 and 10 μL of 100 μM H2O2 under visible light for 10 minutes. SD rats were divided into 5 groups, 3 rats in each group. The wound conditions were photographed and recorded every day. The rats were killed on the 10th day, and the wound tissues were collected, stored in 10% formalin, embedded in paraffin, sectioned, stained with HE, and processed for immunohistochemistry. After 14 days, they were observed using an ordinary upright fluorescence microscope.
[0048] 14. Data Analysis
[0049] The wound area, colony counts, and scratch width of rats were quantitatively analyzed by Image J 1.46. The data were from three independent experiments, and the error bars represent mean ± standard deviation. Data were analyzed using Origin 2023 or GraphPad Prism 8. Statistical significance was determined using two-tailed Student's t-test and one-way analysis of variance (ANOVA), *P < 0.05, **P < 0.01, ***P < 0.001, ****P < 0.0001 indicated statistical significance between groups.
[0050] 15. Experimental Results
[0051] (1) The present invention uses a simple one-step hydrothermal method to synthesize three-dimensional (3D) flower-shaped nanozymes Co(OH)2 and CuCo(OH)2. 2+ (and Cu 2+ ) ions undergo a hydrolysis process to form hydroxide-like compounds and further grow, eventually forming a three-dimensional hierarchical flower-like structure with extremely thin and corrugated nanosheets. Scanning electron microscopy (SEM) images of Co(OH)2 show a blooming flower-like morphology, such as Figure 2 The SEM image shown in (a) in 2 shows that the introduction of copper metal ions did not change the overall morphology, but led to the formation of a bimetallic layered flower-like structure. The transmission electron microscopy (TEM) image of CuCo(OH)2 shows that the three-dimensional layered flower-like structure is composed of ultrathin nanosheets with smooth surfaces, as shown in Figure 2. Figure 2 Middle (b). Figure 2The high-resolution TEM (HRTEM) image shown in (c) further demonstrates the good crystal structure of CuCo(OH)2. Through elemental mapping and energy dispersive spectroscopy (EDS), the present invention confirms the uniform distribution of oxygen, cobalt, and copper in CuCo(OH)2, and the copper content is 3.96%, proving that copper has been successfully incorporated. Figure 2 Middle (d) and Figure 3 shown.
[0052] The crystal structures of Co(OH)2 and CuCo(OH)2 were further analyzed by X-ray diffraction (XRD). Figure 2 (e) shows that the physical phases of Co(OH)2 and CuCo(OH)2 conform to the cubic spinel structure of Co(OH)2 (PDF#: 46-0605). Since the atomic radii of copper and cobalt atoms are similar, the incorporation of copper has little effect on the crystal phase of Co(OH)2. X-ray photoelectron spectroscopy (XPS) further reveals the effect of copper incorporation on the electronic structure of Co(OH)2. Figure 4 The XPS spectrum of CuCo(OH)2 shows that the characteristic peaks of copper, cobalt and oxygen are obvious, while Co(OH)2 only has peaks of cobalt and oxygen. The peaks of copper are 932.6 eV, 935.7 eV and 943.4 eV, corresponding to Cu + , Cu 2+ and the corresponding satellite peaks, such as Figure 1 Middle (f). Figure 2 The high-resolution Co 2p spectra shown in (g) show that Co in Co(OH)2 and CuCo(OH)2 2+ (784.4 eV and 784.1 eV) and Co 3+ (781.3 eV and 781.1 eV) corresponding to the satellite peaks. Figure 5 The O 1s spectrum shown indicates that lattice oxygen (531.4 eV) and oxygen vacancy (Ov) (532.0 eV) species are present in all samples, and the area of Ov in CuCo(OH)2 is significantly larger than that in Co(OH)2, indicating that a large number of oxygen vacancies are generated after copper doping.
[0053] (2) In order to verify the enhancement effect of Cu doping Co(OH)2 on its POD-like activity and optical properties, the present invention tested the POD-like activity of Co(OH)2 and CuCo(OH)2 under visible light irradiation. The absorbance at 652 nm was measured by catalyzing the oxidation reaction of 3,3′,5,5′-tetramethylbenzidine (TMB) substrate in the presence of H2O2. Figure 6The results shown in (a) show that the POD-like activity of CuCo(OH)2 is significantly improved compared with that of Co(OH)2. Under visible light irradiation, its POD-like activity is significantly enhanced, while the change of Co(OH)2 is small. This shows that CuCo(OH)2 has better visible light catalytic performance. Through electron spin resonance (EPR) and ultraviolet-visible reflectance spectroscopy (UV-Vis) tests, the present invention further found that CuCo(OH)2 has a higher oxygen vacancy content and a stronger ability to absorb visible light, such as Figure 6 These results indicate that after Cu is doped into Co(OH)2, the formation of oxygen vacancies promotes the adsorption of H2O2, which in turn enhances the transfer of photogenerated electrons in the CuCo(OH)2 system and promotes the generation of •OH.
[0054] (3) In order to further reveal the type and rate of ROS generation catalyzed by CuCo(OH)2 and Co(OH)2, a series of EPR tests were performed. 5,5-dimethyl-1-pyrroline-N-oxide (DMPO) and 2,2,6,6-tetramethyl-4-piperidinol (TEMP) were used to capture •OH, O2• - and 1 The generation of O2. Figure 6 The test results shown in (d)-(f) show that the amount of •OH generated by CuCo(OH)2 under visible light irradiation is significantly higher than that of Co(OH)2, proving that CuCo(OH)2 has stronger POD-like activity. In addition, CuCo(OH)2 also produces O2• more efficiently than Co(OH)2. - and 1 O2, which indicates that CuCo(OH)2 has stronger photoelectron transfer and free radical generation capabilities.
[0055] (4) To verify the antibacterial effect of CuCo(OH)2 on common drug-resistant bacteria (such as ESBL-producing Escherichia coli) in vitro, the present invention conducted antibacterial performance tests under different experimental conditions. The results showed that under visible light irradiation, CuCo(OH)2 could effectively eliminate ESBL-producing Escherichia coli at a concentration of 12.5 μg / mL, with a bactericidal rate of more than 99.9999%. Figure 7 (a) and Figure 8 As shown, it shows its excellent antibacterial properties. Through laser confocal microscopy (LCSM) observation, it was found that CuCo(OH)2 can destroy the bacterial membrane, and the charge interaction between CuCo(OH)2 and the bacterial membrane causes the bacteria to aggregate on the surface of the nanozyme, such as Figure 7 As shown in (b) and (c), DNA agarose gel electrophoresis and protein leakage experiments showed that ROS caused severe damage to bacterial DNA, ultimately leading to cell death. Figure 7(5) Further cytotoxicity experiments showed that CuCo(OH)2 had no significant toxic effect on fibroblasts (L929), as shown in (7) (f).
[0056] (6) To evaluate the role of nanozymes in the actual healing process of bacterial-infected wounds, an ESBL-producing Escherichia coli-infected wound model was established in 6-week-old Sprague-Dawley (SD) rats. Representative images of the treated wounds and their surrounding areas on days 0, 2, 4, 6, 8, and 10 are shown. The rats in the CuCo (OH)2 / H2O2 / light-treated group had the highest degree of wound healing and the highest wound repair rate (Figure 9 (a) and (c)). On day 10, bacterial count results showed that the CuCo (OH)2 / H2O2 / light-treated group had almost eliminated all bacteria around the wound, while live bacteria still remained in the wounds of the other groups, such as Fig. 9 (b) 5 and (d). As re-epithelialization is an important process of wound healing, hematoxylin-eosin (H&E) staining was performed on the wound tissues of rats on day 10 to further evaluate the wound healing process. In the CuCo(OH)2 / H2O2 / light group, inflammatory cell infiltration was reduced, granulation tissue was generated, and the skin layer was intact, indicating that wound re-epithelialization was enhanced and the treatment effect was significant, as shown in (e) of Figure 9.
[0057] The expression of related cytokines in the wound skin healing process was further studied by immunohistochemistry, e.g. Fig. 9As shown in (f). Tumor necrosis factor α (TNF-α) was used as a marker to study collagen formation and inflammatory conditions in the wound site. The expression of TNF-α was the lowest in the CuCo (OH)2 / H2O2 / light-treated group, indicating that inflammation was almost completely resolved, which was consistent with the results of hematoxylin-eosin (H&E) staining. Vascular endothelial growth factor α (VEGF-α) can promote angiogenesis, which is particularly important in the wound healing process, and CD31, also known as platelet endothelial cell adhesion molecule 1, is a marker of angiogenic ability. The expression of VEGF-α and CD31 was significantly increased in the CuCo (OH)2 / H2O2 / light-treated group compared with other control groups. These results suggest that CuCo (OH)2 / H2O2 / light has the potential to promote angiogenesis in fibrotic tissue and thus promote wound healing. In addition, the tissue morphology of several important organs such as heart, liver, spleen, lung and kidney was studied by hematoxylin-eosin (H&E) staining. As shown in Figure 9 (g), no organ damage or histological lesions were observed in all groups of mice after 10 days. This shows that CuCo (OH)2 is non-toxic and harmless, and its excellent biocompatibility means that it has broad application prospects in the field of biomedical science.
Claims
1. A nanozyme for photocatalytic cascade enhanced peroxidase reaction, characterized in that: The nanozyme is a copper-doped nanozyme CuCo(OH)2, wherein the doping amount of Cu in CuCo(OH)2 is 3-5%.
2. The nanozyme for photocatalytic cascade enhanced peroxidase reaction according to claim 1, characterized in that: The doping amount of Cu in CuCo(OH)2 is 3.96%.
3. The method for preparing the nanozyme according to claim 1, characterized in that: include: Dissolve Co(NO3)2•6H2O and Cu(NO3)2•3H2O in methanol, and dissolve 2-methylimidazole in methanol; then quickly pour the 2-methylimidazole solution into the solution containing Co. 2+ and Cu 2+ The mixture was added to a solution and stirred evenly with a magnetic stirrer; in the reaction system, the final concentration of Co(NO3)2•6H2O was 50-100 mmol / L, the final concentration of Cu(NO3)2•3H2O was 20-50 mmol / L, and the final concentration of 2-methylimidazole was 150-200 mmol / L; the mixed solution was then transferred to a PTFE-lined stainless steel autoclave and heated at 120°C for 2 hours; after cooling to room temperature, the precipitate was washed several times with methanol by centrifugation, and then dried at 60°C to collect the yellow product.
4. The use of the nanozyme according to claim 1, characterized in that: Application of the nanozyme in preparing an antibacterial composition.
5. The use according to claim 4, characterized in that: The nanozyme is used in preparing a composition for resisting drug-resistant bacteria.
6. An antibacterial composition, characterized in that: The composition comprises an effective dose of the nanozyme according to claim 1 or 2, wherein the nanozyme promotes the generation of ROS in the photocatalytic cascade enhanced POD reaction.
Citation Information
Patent Citations
Copper-cobalt-sulfur nano-enzyme material as well as preparation method and antibacterial application thereof
CN111217401A
Copper-cobalt bimetal organic framework nano-enzyme and colorimetric analysis method of organic phosphorus colorimetric sensor of copper-cobalt bimetal organic framework nano-enzyme
CN114835913A
Preparation method and application of photoacoustic enhanced multi-enzyme activity nano-enzyme hydrogel
CN115501335A
Copper nanosheet-containing nano-enzyme capable of sterilizing and promoting wound repair as well as preparation method and application of copper nanosheet-containing nano-enzyme
CN116173069A
Preparation and application of bimetallic nano-enzyme capable of enhancing peroxidase activity
CN118787662A